1996
DOI: 10.1002/hep.510240331
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of lipid peroxidation in plasma membrane in two experimental models of liver regeneration: Partial hepatectomy and acute CCl4administration

Abstract: with the rate of mitosis in several tissues, which has been It has been proposed that lipid peroxidation (LP) supported by the decreased LP found in subcellular fractions might be a modulator of cell division, influencing initiaof liver tumor cells. [2][3][4] However, some discrepancies have been tion and cessation of mitosis in regenerating liver. Howraised concerning the LP status during the characteristic acever, the understanding of the participating role of this tive cell proliferation following partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…It has been found that LP began to occur in a very early phase in regenerating liver [32,33]. Actually, some discrepancies still exist concerning the role of LP during typical cell proliferation following PH [34]. It has been reported that diminished LP contributes to cell division after PH [35, Bicyclol (300 mg/kg) was administrated three times before operation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that LP began to occur in a very early phase in regenerating liver [32,33]. Actually, some discrepancies still exist concerning the role of LP during typical cell proliferation following PH [34]. It has been reported that diminished LP contributes to cell division after PH [35, Bicyclol (300 mg/kg) was administrated three times before operation.…”
Section: Discussionmentioning
confidence: 99%
“…Variable levels of LP in the various subcellular fractions have also been reported (19). For example, there is decreased lipid peroxidation in microsomes and increase in the plasma membrane and cytosolic fractions of normal (well-fed) rats following Partial hepactectomy (19).…”
Section: Discussionmentioning
confidence: 95%
“…For example, there is decreased lipid peroxidation in microsomes and increase in the plasma membrane and cytosolic fractions of normal (well-fed) rats following Partial hepactectomy (19). There are, however, little or no reports in the literature concerning changes in the levels …”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, it is reported that PUT promotes DNA synthesis in regenerating liver after PH through the suppression of lipid peroxidation in subcellular fractions. 34 The lipid peroxidation is found at early stages of regeneration after PH, and inversely correlates with the rate of DNA synthesis. [34][35][36] Therefore, Gln-PUT increase after PH may also be involved in the regulation of DNA synthesis.…”
Section: The Effect Of Ra On the Formation Of Protein-polyamine Bond mentioning
confidence: 99%
“…34 The lipid peroxidation is found at early stages of regeneration after PH, and inversely correlates with the rate of DNA synthesis. [34][35][36] Therefore, Gln-PUT increase after PH may also be involved in the regulation of DNA synthesis. Shortly after PH, the EGF plasma level becomes elevated two to three-fold, 37 therefore, the activation of EGF receptors is likely to be involved in G1 phase progression during liver regenerative growth.…”
Section: The Effect Of Ra On the Formation Of Protein-polyamine Bond mentioning
confidence: 99%